2021
DOI: 10.1093/europace/euab116.549
|View full text |Cite
|
Sign up to set email alerts
|

Repolarization characteristics indicate electrical instability in ventricular arrhythmia originating from papillary muscle

Abstract: Funding Acknowledgements Type of funding sources: Public grant(s) – National budget only. Main funding source(s): DZHK (German Center for Cardiovascular Research) Introduction Cardiac arrhythmia originating from the papillary muscle can trigger ventricular fibrillation and cause sudden cardiac death even in the absence of structural heart disease. Yet, no clinical parameters are known to reflect the propensity of arrhythmia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The PVC/VT, originating from the left posterior papillary muscle, did not need high pressure and long discharge time to achieve the ideal effect. Excessive ablation at the papillary muscle might have caused poor papillary muscle function or ventricular fibrillation (Muenkler et al, 2021 ; Nishiyama et al, 2017 ). Moreover, this study found that there were sharp potential and potential reversal at the ablation target, which helped to identify the effective target.…”
Section: Discussionmentioning
confidence: 99%
“…The PVC/VT, originating from the left posterior papillary muscle, did not need high pressure and long discharge time to achieve the ideal effect. Excessive ablation at the papillary muscle might have caused poor papillary muscle function or ventricular fibrillation (Muenkler et al, 2021 ; Nishiyama et al, 2017 ). Moreover, this study found that there were sharp potential and potential reversal at the ablation target, which helped to identify the effective target.…”
Section: Discussionmentioning
confidence: 99%